Clinical Outcomes in Patients Receiving Originator Follitropin Alfa and Follitropin Alfa Biosimilars in Real-world Clinical Practice: A Retrospective Study - Nayana Hitesh Patel; Niket H. Patel; Molina Niket Patel; Harsha K. Bhadarka; Kairavi Sunilkumar Vyas (Journal of Human Reproductive Sciences)
Background: Biosimilar drugs have broadened the treatment options in assisted reproductive technology (ART). Real-world data comparing clinical outcomes of originator follitropin alfa (Gonal-f®) with its biosimilars are required to enrich the body of evidence for clinical decision-making on choice of drug. Aims: To compare the ART outcomes in patients receiving originator follitropin (Gonal-f®) and its biosimilars in clinical setting. Settings and Design: Medical records of 364 infertile women who underwent ART between 2016 and 2020 at Akanksha Hospital and Research Institute, Gujrat, India, were retrospectively analysed. Materials and Methods: Participants were divided into two cohorts based on treatment (Gonal-f® cohort; N = 174 and biosimilar cohort; N = 190), each cohort further subdivided into group A (age <35 years) and group B (age ≥35 years). Fresh or frozen embryo transfer was performed as per the standard procedures of the clinic. Pregnancy rates and live birth rate (LBR) were the primary main outcome measures in this study. Statistical Analysis Used: Descriptive statistics and Chi-square test were used for analysis. Results: The number of oocytes retrieved from Gonal-f® and biosimilar cohorts were comparable (13.3 vs. 14.4). Compared to biosimilars, Gonal-f® treatment resulted in higher yield of cleavage stage and blastocyst stage embryos, and the proportion of women with good quality embryos was higher in the Gonal-f® cohort than the biosimilar cohort (83.3% vs. 69.5%). Patients receiving Gonal-f® reported higher pregnancy rates (59.2% vs. 39.7%) and LBR (43% vs. 17.7%) compared to those receiving biosimilars. Conclusions: Gonal-f® (originator follitropin) treatment could result in higher pregnancy rates and LBR in comparison to biosimilars in real-world setting.